2019
DOI: 10.3329/ganit.v39i0.44165
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Treatment on HIV-Malaria CoInfection Based on Mathematical Modeling

Abstract: The distribution of HIV and malaria overlap globally. So there is always a chance of co-infection. In this paper the impact of medication on HIV-Malaria co-infection has been analyzed and we have developed a mathematical model using the idea of the models of Mukandavire, et al. [13] and Barley, et al. [3] where treatment classes are included. The disease-free equilibrium (DFE) of the HIV-only model is globally-asymptotically stable (GAS) when the reproduction number is less than one. But it is shown that in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…Several articles employ these methods, incorporating different types of prevention and intervention controls. 28 , 31 , 34 , 38 , 39 , 45 , 49 , 58 Certain articles determine the best strategy to reduce infection by altering parameter values. 26 , 33 , 40 However, some articles did not incorporate any control measures in their analysis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several articles employ these methods, incorporating different types of prevention and intervention controls. 28 , 31 , 34 , 38 , 39 , 45 , 49 , 58 Certain articles determine the best strategy to reduce infection by altering parameter values. 26 , 33 , 40 However, some articles did not incorporate any control measures in their analysis.…”
Section: Resultsmentioning
confidence: 99%
“…According to 30 article, the most effective method to diminish malaria-HIV coinfection involves the combination of malaria prevention measures and antiretroviral (ARV) treatment. However, 31 article obtained the result that treating malaria and HIV individually proved to be more effective in reducing infection compared to administering combined treatment. 28 The escalation of HIV/AIDS prevalence due to coinfection with malaria, highlights the significance of treatment in mitigating this interplay, particularly for individuals already affected by AIDS.…”
Section: Resultsmentioning
confidence: 99%
“…[7] To understand the paraphernalia responsible for these effects of coinfection, an immunoepidemiological model was formulated. [12] They found that populations with higher spVL lead to higher increases in viral load due to coinfection, whereas populations with lower spVL lead to reduction in viral load due to coinfection. This leads to a greater chance of coinfection increasing the occurrence of HIV in populations with high average spVL.…”
Section: Introductionmentioning
confidence: 99%
“…This leads to a greater chance of coinfection increasing the occurrence of HIV in populations with high average spVL. [12] Therefore, the result of coinfection may be eased by sensing the viral factors that can shrink the spVL in the population. HIV immunoepidemiologic models syndicate the immune-viral dynamics at the within-host immunological scale with the transmission dynamics at the between-host epidemiological scale to analyze HIV dynamics of a single strain infection, coinfection, super-infection, evolution, drug resistance, and treatment protocols in heterogeneous populations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, this infection has no curing medication, but antiretroviral therapy (ART) or its combination is used for halting further progression of infection by inhibiting the virus in human blood, but if left untreated leads to a sever stage called acquired immunodeficiency syndrome (AIDS) [12][13][14][15][16][17][18][19][20][21][22][23]. HIV infection progress through stages as follows: (i) primary stage (asymptomatic stage): this stage faces human individual where the virus is in the blood cannot be diagnosed with medical instruments; (ii) asymptomatic stage: this stage is symptomless stage of HIV infection but diagnosable with medical test; (iii) symptomatic stage: in this stage, the symptom of HIV infection like tiredness, loss of weight, and extreme loss of water starts to manifest in the life of HIV infected individuals; and (iv) AIDS stage: this is advanced stage of HIV infection where it is difficult for treatment and leads to death soon if special care is not taken [24][25][26][27][28][29][30][31][32]. Modes of HIV transmission are through unsafe sexual practices with HIV-infected person, through contacts of normal blood with HIV infected blood, mother to child through breast or birth time, and any contacts of HIV contains fluids of human's with HIV-negative human fluids [33][34][35].…”
Section: Introductionmentioning
confidence: 99%